1997
DOI: 10.1177/030089169708300228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Long-Term Survival in Patients with Glioblastoma Multiforme

Abstract: Repeated reports of more than ten years postoperative survival in patients with glioblastoma multiforme (GM) have appeared in the literature over the last decades. Authors have tried to identify the clinical, therapeutic and histological features determining long-term survival. We present two patients in whom, after radical removal of the tumor followed by conventional radiation, there has been no recurrence for at least ten years. The young age of the patients and the radical surgical approach were in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…13,15 However, this study has confirmed a highly significant benefit shown to patients undergoing more radical clearance of tumour as compared with biopsy alone. Similarly, patients receiving higher-dose radiation showed a significant survival advantage.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…13,15 However, this study has confirmed a highly significant benefit shown to patients undergoing more radical clearance of tumour as compared with biopsy alone. Similarly, patients receiving higher-dose radiation showed a significant survival advantage.…”
Section: Discussionmentioning
confidence: 51%
“…These findings are consistent with other reports. [10][11][12][13] Age in this series played a significant role with half the series being younger than 60 years and revealing approximately double the survival (1 year: 42% vs. 23%) of those aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…Factors correlated to the long survival rates reported in the literature are radical surgical resection, young age at onset, complementary treatments, and good clinical status at the time of diagnosis [5,49,50]. Nonetheless, objective prognosis of patients with anaplastic glioma is difficult to determine at the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Steiger, et al reported 14 patients with thalamic gliomas, 10 with high grade (grade three and four) gliomas upon whom STR or GTR was attempted through a parieto-occipital transventricular approach with an acceptable morbidity profile (two among 14 had new partial hemianopia) [ 3 ]. In some other case reports, these attempts have resulted in outstanding results [ 5 , 10 ]. Kelly suggested surgery (as opposed to stereotactic biopsy followed by adjuvant therapy) in those suffering from an enlarging tumor with significant mass effect, or in those with recurring cysts [ 6 ].…”
Section: Discussionmentioning
confidence: 99%